Мовностилістичні особливості молитви у конфесійному стилі української мови - Жалко, Тетяна; Zhalko, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті основна увага зосереджена на понятті «молитва» як провідному жанрі конфесійного стилю української мови та його мовностилістичних особливостях. Наголошується, що релігія, як і мова, є органічною частиною духовного життя етносу. Основні акценти зроблено на лексиці й тропеїчній образності релігійних молитов, які за своїм функціональним навантаженням багаті й своєрідні. The article deals with the peculiarities of confessional style that serves the scope of religious and church life. Basic attention is focused on the concept of «prayer», which is the leading genre of confessional style of Ukrainian language, and its linguistic and stylistic peculiarities. It is stressed that religion, like language, is an integral part of the spiritual life of the ethnic group and modern conditions actively promote the full development of all means of language organization of style scope of religious and church cult. The focus is made on the vocabulary of religious prayers, which are inherently rich and distinctive. It is diverse by origin, to the context of sacral works skillfully woven numerous examples of synonyms and antonyms, its means are substantially represented by tropes figurativeness and labeled elements.
Linguistic and Stylistic Peculiarities of Prayer in Confessional Style of Ukrainian Language
Keywords: конфесійний стиль; молитва; стилетворчі засоби; сакральна мова; стилістеми; confessional style; prayer; style creative means; sacral language; style systems